2021
DOI: 10.3390/children8060459
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors as a Cause of Differences in the Feet of Ecuadorian Children and Its Relation to Their Footwear

Abstract: The objective of this study was to analyze the differences in foot measurements of Ecuadorian children according to their geographical location of residence, taking into account climatic differences (1). A total of 1662 children (2) participated in the study. Three groups were established: coast, mountains and amazonia. The type of footwear (3) used was recorded and the lengths, widths, perimeters, heights and angles of both (4) feet were analyzed with a 3D foot digitizer (5). The variable ‘fitting of the foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(40 reference statements)
0
6
1
Order By: Relevance
“…Like Klein et al we have detected a worse fit in shoe length in the boys of our sample, however contrary to the results reported by these authors, our results show a slightly higher average of HVA in the girls although without significant differences [9]. As in previous studies, we have observed a strong correlation between poorly fitting footwear and increased HVA in schoolchildren of both sexes in ages of onset pubertal foot growth, especially in girls [9,13]. The highest average value of HVA was recorded in the footwear category considered short.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Like Klein et al we have detected a worse fit in shoe length in the boys of our sample, however contrary to the results reported by these authors, our results show a slightly higher average of HVA in the girls although without significant differences [9]. As in previous studies, we have observed a strong correlation between poorly fitting footwear and increased HVA in schoolchildren of both sexes in ages of onset pubertal foot growth, especially in girls [9,13]. The highest average value of HVA was recorded in the footwear category considered short.…”
Section: Discussioncontrasting
confidence: 80%
“…According to previous studies, specific problems (pain, hallux valgus, claw toes or skin changes) have been detected in the feet of children who used inappropriate footwear) [10,11]. Similarly, the use of ill-fitting footwear seems to be related to the development of hallux valgus in schoolchildren [9][10][11][12][13][14][15]. This current study aims to evaluate the influence that an inadequate footwear fit in schoolchildren can have on the development of the deformity and establish if there is a correlation between the use of poorly fitting outdoor footwear and the development of hallux valgus in a sample of schoolchildren from southern Spain.…”
Section: Introductionmentioning
confidence: 94%
“…Aibast et al [10] studied habitually barefoot children of the Kalenjin tribe in Kenya and found that the combination of high levels of physical activity and a barefoot lifestyle resulted in stronger foot muscle strength, ligaments, and tendons. Furthermore, studies comparing children living in the mountains or the Amazon with Ecuadorian children living on the coast have found that coastal Ecuadorian children have longer, wider feet, larger girth, and higher arches [59]. Previous studies reported that children habitually barefoot had longer, wider feet and higher arches than children habitually shod [6,[9][10][11]59,60].…”
Section: Children's Footwear Effect On Footmentioning
confidence: 99%
“…The hallux valgus angle (HVA), also called first metatarsophalangeal angle, first toe angle, or toe #1 angle, is the most significantly different measurement between habitually shod and barefoot population [1]. Shoe toe box shape [2], opened-toed versus closed-toed shoes [3] and shoe fitting [4] are essential factors influencing HVA to increase. Hallux valgus angle is related to plantar pressure during walking and running [1].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of 3D scanning and CAD tools, efforts have been made to utilize these technologies in foot morphology studies and footwear design. Previous studies that have quantitatively evaluated the HVA either need palpation landmarks of feet before scanning [14,15,11,3], or manual adjustments of tangent lines on 3D scans [12,16,17].…”
Section: Introductionmentioning
confidence: 99%